Corrugation-like Triboelectric Nanogenerators Integrated Buoys for Wave Energy Harvesting - Guan, Tangzhen; Wang, Weichen; Wang, Xinyu; Wen, Chengxuan; Xu, Ruijiang; Zhu, Chuanqing; Zou, Tao; Zheng, Jiaxi; Xu, Minyi; Wang, Hao (Journal of physics. Conference series, 2023)
Marine buoys, as the nodes of the marine monitoring system, play a vital role in monitoring marine activities, which can collect hydro-meteorological information for marine scientific research, offshore oil development, and construction of marine ports. However, sustainable and cost-effective power supply for marine buoys equipped with electrical devices is still a challenge. In this paper, the corrugation-like triboelectric nanogenerator (C-TENG) integrated with marine buoys was proposed, aiming at harvesting wave energy and powering marine buoys. The C-TENG consisting of corrugated plates, corrugation-like channels, aluminum electrodes, barrier sheets, flat plates, and polytetrafluoroethylene (PTFE) pellets, was capable of effectively converting the energy harnessed from waves into electricity. As a result of the ocean wave’s excitement, the sliding contact between the PTFE pellets and the aluminum electrode produced electron transfer via the triboelectrification effect and electrostatic induction. With the unique corrugation-like channels, the output of the devices was in the same phase, avoiding the electrical loss resulting from rectification. Furthermore, the power density of the 5 layers parallel-connected C-TENG units reached 21.95 W/m 3 , which was approximately 300% higher than the previous tower-like TENG. The experimental results prove that the proposed C-TENG may provide a possible solution for wave energy harvesting and marine buoy powering.